Effect of the spatial heterogeneity on the predation of Scinax fuscovarius and Physalaemus cuvieri tadpoles by Odonata larvae = Efeito da heterogeneidade ambiental na predação de girinos de Scinax fuscovarius e Physalaemus cuvieri por larvas de Odonata - João Ânderson Fulan; Silvio César Almeida (Acta Scientiarum: Biological Sciences, 2010)
The objective of this work were to analyze the effect of predation byOdonata naiads on two amphibian species with distinct habits – benthic and mid-water – and to verify whether the presence and architecture of macrophytes can mediate this interaction. All tadpoles and Odonata larvae were captured in a temporary pond. Sixteentanks were used for three different treatments: Pistia, Salvinia and no macrophytes. Ten tadpoles of each species and two Odonata larvae were placed in each tank. The survival of tadpoles according to treatments was assessed through analysis of repeated measures. Weconcluded that the survival of P. cuvieri and S. fuscovarius tadpoles was not affected by the presence and architecture of the macrophytes (Pistia and Salvinia) or by their behavior. Os objetivos deste trabalho foram analisar o efeito da predação por náiades de Odonata em duas espécies de anfíbios com hábitos distintos, um bentônico e outro meia-água, e verificar se a presença e a arquitetura das macrófitas podem mediar essa interação. Todos os girinos bem como as larvas de Odonata foram capturados em poça temporária. Dezesseis aquários foram utilizados nos três diferentes tratamentos: Pistia, Salvinia e sem macrófitas. Dez girinos de cada espécie e duas larvas de Odonata foram colocados em cada aquário. Uma análise de medidas repetidas foi realizada para se determinar a sobrevivência dos girinos em função dos tratamentos. Concluímos que a sobrevivência dos girinos de P. cuvieri e S. fuscovarius não foi afetada pela presença e arquitetura das macrófitas (Pistia e Salvinia) nem pelo seu comportamento.